Pengembangan Norma Penilaian Tes Endurance Atlet Renang KU 1 DIY Berbasis Multistage - Falaahudin, Ardhika; Supriyanto, Agus; Ambardini, Rachmah Laksmi; Potutu, Nizar Raihan; Putra, Afroga Muhhakat Destri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to develop multistage-based endurance test norms for KU 1 swimming athletes that are packaged in an easy, measurable, and field-applicable manner. This research falls into the category of development research or Research and Development (R&D). Data analysis in this study uses quantitative descriptive methods. From the research, the results obtained are the assessment norm categories: "inferior" in the interval of 3.5-4.0 test level scale, "poor" in the interval of 4.0-4.6 test level scale, "sufficient" in the interval of 4.6-5.1 test level scale, "good" in the interval of 5.1-5.7 test level scale, and "very good" in the interval of 5.7-6.2 test level scale. So, this research concludes that a product has been developed in the form of the Development of Endurance Test Assessment Norms for Swimming Athletes KU 1 DIY Based on Multistage. The development assumption used in this research is that it can make it easier for coaches to provide training programs and independent physical training for swimming athletes. The limitation of the product Development of Endurance Test Assessment Norms for KU 1 DIY Swimming Athletes Based on Multistage is proposed only for the Yogyakarta region, so the research sample was obtained only from athletes residing in Yogyakarta. In conclusion, there is a developed product in the form of the Development of Endurance Test Assessment Norms for Swimming Athletes KU 1 DIY Based on Multistage. Keywords: Assessment Norms, Athletes, Endurance Test, Multistage, Swimming